2018
DOI: 10.1016/j.hrthm.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Permanent His bundle pacing: Recommendations from a Multicenter His Bundle Pacing Collaborative Working Group for standardization of definitions, implant measurements, and follow-up

Abstract: His bundle pacing (HBP) prevents ventricular dyssynchrony and its long-term consequences by preserving normal electrical activation of the ventricles. Since the original description of permanent HBP in 2000, the adoption of HBP has increased over the past several years. However, the reporting of procedural and clinical outcomes to date is not uniform. This article is a collaboration between several implanters with significant experience in HBP to establish a uniform set of definitions encompassing the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
244
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(259 citation statements)
references
References 23 publications
4
244
0
11
Order By: Relevance
“…There was no ECG core lab for confirming His capture; therefore the presence and type of His bundle capture were verified by the implanting physician according to the accepted criteria published in the His pacing consensus document . The method for measuring QRS duration was determined by the local protocol within each institution.…”
Section: Discussionmentioning
confidence: 99%
“…There was no ECG core lab for confirming His capture; therefore the presence and type of His bundle capture were verified by the implanting physician according to the accepted criteria published in the His pacing consensus document . The method for measuring QRS duration was determined by the local protocol within each institution.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for HBP were used as described in the Recommendations of the Collaborative Working Group 13. Successful correction of LBBB was defined by paced ECG morphology without LBBB manifestation.…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies described selective and nonselective HBP, there is no report of prospectively looking at the association of HBP pattern and the location of HBP. This investigation found that when the pacing lead tip was placed on the atrial side of the His bundle, His bundle capture was selective, and the selective HBP remained even when the pacing output was significantly increased to 5 V. This finding suggests that the pacing electrical current failed to penetrate through the atrioventricular septum and reach the myocardial tissue in the basal IVS.…”
Section: Discussionmentioning
confidence: 99%
“…Capture threshold test was performed, starting at 5 V @ 1 ms output with decrement until loss of capture to assess HBP characteristics. The criteria for selective and nonselective HBP were based on the literature definition …”
Section: Methodsmentioning
confidence: 99%